2018
DOI: 10.2478/acve-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Q Fever and Brucellosis in Aborted Ovine Fetuses by Microbiological, Pathological and Immunohistochemical Methods

Abstract: Brucellosis and Q fever, two zoonoses, are important causes of abortion in ruminants, as well as economically significant diseases caused by a gram-negative bacterium. Determination of these diseases is therefore of great importance. In this study, the organs of 35 naturally infected and aborted ovine fetuses were examined for the presence of changes resulting from infections by Brucella melitensis and Coxiella burnetii, according to macroscopic, bacteriological, histopathological and immunohistochemical metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The statistical analysis revealed that age is not a significant risk factor. This result coincides with the results of the previous study ( 37 ). It can be assumed that the way of keeping the herds (mixed age group and species) results in chronic infection of the herd and infection pressure on the individual animal independent of its age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The statistical analysis revealed that age is not a significant risk factor. This result coincides with the results of the previous study ( 37 ). It can be assumed that the way of keeping the herds (mixed age group and species) results in chronic infection of the herd and infection pressure on the individual animal independent of its age.…”
Section: Discussionsupporting
confidence: 93%
“…In Pakistan, data on the geographic distribution of Q fever based on epidemiological surveillance studies are limited for livestock and humans. In the current research, the prevalence of C. burnetii infection, i.e., the seroprevalence in small ruminants, has been investigated using indirect ELISA, the serodiagnostic technique is preferably used for screening as it is more sensitive and specific than any other serological technique ( 35 37 ) reported 100% sensitivity and specificity for the applied IDVET® Q fever Indirect ELISA. Thus, 13.0% sero-epidemiology of the pathogen in district Jhang is a significant finding concerning future disease management in animals and humans.…”
Section: Discussionmentioning
confidence: 99%